CHASERR-CHD2 dynamics in T cell quiescence and its modulation by cyclosporine - Budkina, Anna; Zubritskiy, Anatoliy; Marakulina, Daria; Loguinova, Marina Yu.; Sergeev, Nikita A.; Medvedeva, Yulia A. (Frontiers in Immunology, 2025)
BackgroundCHASERR, a conserved long non-coding RNA located upstream of CHD2, transcriptionally represses CHD2 in cis. Both genes are highly expressed in lymphocytes, suggesting roles in immune regulation, though their functions remain undefined.ResultsWe identified elevated expression of CHASERR and CHD2 in naïve and regulatory T cells through analysis of single-cell and bulk RNA-seq datasets. Both their promoters are bound by FOXP3, the key regulator of Treg cells, and FOXP1, the key regulator of naïve T cell quiescence. Expression dynamics during early T cell activation revealed that a decline in CHASERR precedes a transient increase in CHD2. Correlation analysis linked CHASERR/CHD2 expression to quiescence-associated genes, suggesting a role in maintaining T cell homeostasis. We predicted and experimentally validated that cyclosporine A, a calcineurin inhibitor and potent immunosuppressant, mitigates the transcriptional changes induced by CHASERR loss, notably reducing elevated CHD2 expression in vitro after CHASERR knockdown.ConclusionsOur results position the CHASERR-CHD2 axis as a potential regulator of T cell homeostasis and activation. Furthermore, we propose cyclosporine A as a potential therapeutic strategy for conditions involving CHASERR deficiency.